Fostering natural forest regeneration on former agricultural land through economic and policy interventions - Chazdon, R.; Lindenmayer, D.; Guariguata, Manuel R.; Crouzeilles, R.; Rey Benayas, J.M.; Chavero, E.L. (IOP Publishing, 2020)
Under suitable conditions, deforested land used for agricultural crops or pastures can revert to forest through the assisted or unassisted process of natural regeneration. These naturally regenerating forests conserve biodiversity, provide a wide array of ecosystem goods and services, and support rural economies and livelihoods. Based on studies in tropical and temperate forest ecosystems, we summarize cases where natural regeneration is occurring in agricultural landscapes around the world and identify the socio-ecological factors that favor its development and affect its qualities, outcomes and persistence. We describe how the economic and policy context creates barriers for the development, persistence, and management of naturally regenerating forests, including perverse outcomes of policies intended to enhance protection of native forests. We conclude with recommendations for specific economic and policy interventions at local, national, and global scales to enhance forest natural regeneration and to promote the sustainable management of regrowth forests on former agricultural land while strengthening rural communities and economies.